A study on the cephalometric characteristics of 19-24 year old filipinos exhibiting facial balance & harmony - Quejada, Jaime
Cephalometric is a technique employing oriented radiographs for the purpose of making head measurements. The objectives of the study are to provide confirmatory evidences regarding cephalmetric norms established earlier for the Filipinos to determine whether significant differences exist between subjects judged by portrait artists as possessing normal faces and those similarly judged by orthodontists and to determine the skeletal and/or dental basis for the reported convex profile of Filipino samples. 28 non-orthodontically treated Filipinos possessing complete permanent dentition and acceptable facial balance and profile esthetics were chosen as subjects. The results of the study warrant that cephalometric norms for x adult Filipinos may vary with age. With regard to profile esthetics, Filipino artists professed relatively straight profile when compared to the choices of Filipino orthodontics and the skeletal and dental basis of the re posted convexity of the Filipino profile is due to a relatively pro trusted maxilla coupled with a retreaded mandible and more procurement maxillary and mandibular incissors when compared to Caucasians.